IMPLEMENTASI KURIKULUM MERDEKA PADA PEMBELAJARAN IPAS SD MASARAN 1 - Afifah Ayu Nurjanah, Dinda Asmara Firdausa, Septyana Candra Puspita Candra, Nimas Tri Lestari (Elementary School and Education Journal, 2025)
The curriculum plays a vital role in every level of education. This research specifically focuses on examining and understanding the implementation of the Merdeka Curriculum in Integrated Natural and Social Sciences (IPAS) learning at an elementary school. Adopting a descriptive qualitative approach, this study involved the principal and fourth-grade teachers as key informants. Data collection techniques included interviews, observation, and documentation. The collected data were analyzed through reduction, presentation, and conclusion drawing. The research results indicate the success of the elementary school in implementing the Merdeka Curriculum, making it a